



 
Alaa, The expansion follows the distributive laws which say
I am going to expand and simplify a similar expression, (x + 5)(x  3). I want to see this as a(b + c) where a = (x + 5), b = x and c = 3. The first distributive law then gives me
Using the second form of the distributive law on the two terms on the right side of the equation above gives
Finally I can simplify this using the fact that 5x  3x = 2x so I get
Now try (x  9)(x + 2),  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 